DEVELOPMENT OF MATHEMATIC LEARNING MEDIA ON POLYGON MATERIALS BASED ON MACROMEDIA FLASH PROFESSIONAL 8 - Herfiana Alvionita; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The use of instructional media in mathematics learning has not been maximally utilized. The teaching materials used are difficult to understand. The limitations of learning media cause students to feel difficulties in understanding the material. This development research aims to determine the development of mathematics learning media on Polygonmaterial based on Macromedia flash professional eight and the feasibility of mathematics learning media products in supporting mathematics learning on Polygonmaterial. This study uses the Research and Development (R & D) research and development model developed covering the research and data collection stages, planning, developing draft products, initial field trials, and revising trials' results. Subjects in the research and development of learning media were material experts, media experts, and students' responses to MuhammadiyahÂ  Junior High School 2 (SMP 2 Muhammadiyah) Depok andÂ  State Junior High School 4 (SMP Negeri 4) Patuk. This study's object is a medium of learning mathematics of Polygonmaterial based on Macromedia flash professional 8. This learning media has gone through a revision stage based on suggestions and input from material experts and media experts and student responses. The results showed that the assessment by material experts averaged 73.67 with very good categories. The assessment by media experts on average was 51.67 with good categories, and the assessment of student responses averaged 74.92 with excellent categories. These results show that mathematics learning media on Polygonmaterials based on Macromedia Flash Professional 8 is suitable for the learning process and gets positive responses from students.